Preparation and Characterization of Yttrium Oxide Nanoparticles at Different Calcination Temperatures from Yttrium Hydroxide Prepared by Hydrothermal and Hydrothermal microwave Methods - J. Abdulghani, Ahlam; M. Al- Ogedy, Waleed (Iraqi Journal of Science, 2023)
The Synthesis of yttrium oxide nanoparticles have been achieved via calcinationof yttrium hydroxide produced from the reaction of aqueous solutions of yttriumnitrate and sodium hydroxide at pH = 13 using hydrothermal and hydrothermalmicrowave methods. Effect of heat treatment of the resulted yttrium hydroxidepowder on the morphology and crystallinity of the resulting oxide was studied atcalcination 500, 700 and 1000°C to obtain. The resulted products werecharacterized by means of X-ray diffraction (XRD), scanning electron microscope(SEM), atomic force microscope (AFM), Fourier transform infrared spectrometer(FTIR) and thermal analyses (TG).